Influence of the duration of penicillin prescriptions on outcomes for acute sore throat in adults: the DESCARTE prospective cohort study in UK general practice. - Moore, M; Stuart, B; Hobbs, F; Butler, C; Hay, A; Campbell, J; Delaney, B; Broomfield, S; Barratt, P; Hood, K; Everitt, H; Mullee, M; et al. (Royal College of General Practitioners, 2017)
Background Guidelines recommend prolonged treatment courses for acute sore throat but shorter courses may be used in practice. Aim To determine whether antibiotic duration and class predicts adverse outcome of acute sore throat in adults in routine care. Design and setting A secondary analysis of a prospective cohort study of 14610 adults presenting with acute sore throat in primary care. Methods A brief clinical proforma was used to collect symptom severity and examination findings at presentation. Outcomes were collected by notes review and in a sample a symptom diary. Primary outcome: Re-consultation with new/non-resolving symptoms within 1 month. Secondary outcome ‘global’ poorer symptom control (longer than the median duration or higher than median severity). Results Antibiotics were prescribed for 60% (8572/14610) of participants. The most commonly prescribed antibiotic was phenoxymethylpenicillin (76%, 5656/7474) and prescription durations were 5 (20%), 7 (57%), or 10 (22%) days.. Compared with 5 day courses those receiving longer courses were less likely to re-consult with new or worsening symptoms 5 days 15.3%, 7 days 13.9%, 10 days 12.2%, (7 day course adjusted risk ratio 0·92 (0·76, 1·11) and 10 days 0·86 (0·59, 1·23)) but this difference did not reach statistical significance. Conclusions In adults prescribed antibiotics for sore throat, we cannot rule out a small advantage in terms of reduced re-consultation for a 10 day course of penicillin but that effect is likely to be small.